OPTIMIZING SECURE ROUTING PROTOCOLS FOR RESILIENCE NETWORK COMMUNICATIONS - Egho-Promise, Ehigiator; Pervez, Zeeshan; Balisane, Hewa; Asante, George; Aina, Folayo; Kure, Halima (International Journal of Research -GRANTHAALAYAH, 2025)
Routing protocols are very crucial in wired and wireless networks, as they ensure that data packets are efficiently transmitted from a source to their intended destination. These protocols determine the best data route, controlling traffic flow, avoiding congestion, and maintaining communication between routers. Routing protocols are prone to attacks that aim at manipulating or disrupting the operations of the routing protocols. The primary objective of this research is to enhance the security of routing protocols by reducing their vulnerability to attacks while maintaining efficient network performance. A mixed-method approach involving qualitative and quantitative techniques was used. The proposed protocol was compared with BGP, OSPF, AODV, and DSR. Results show that the proposed protocol achieves a high PDR of 95%, while baseline protocols were considerably low, depicting efficiency in terms of the dependability of the protocol to sustain communication in unfavourable scenarios reliably. Besides, the average latency of the proposed protocol is 30 ms, which proves its potential to support time-critical applications that require real-time data delivery. It was observed from the average latency that the value for the proposed protocol was the smallest, about 30 ms, which was sharply different from other protocols; the average latencies for BGP, OSPF, AODV, and DSR were 50 ms, 40 ms, 60 ms, and 55 ms, respectively. The lower latency of the proposed secure routing protocol indicates that it is efficient in packet processing and also capable of supporting applications sensitive to delays like voice and video communication.